Regulatory roles of long non-coding RNAs in minipigs revealed by cross-breed and cross-tissue transcriptomic analyses - Suyeon Wy; Heesun Kim; Minji Gu; Junyoung Kim; Hyeonji Kim; Jiyeong Ahn; Daehong Kwon; Woncheoul Park; Jaebum Kim (Scientific Reports)
Abstract Minipigs are widely used as animal models in biomedical research because they have distinctive advantages, including small body size. However, the regulatory roles of long non-coding RNAs (lncRNAs) in shaping their distinct characteristics remain unexplored. In this study, we performed a comparative transcriptomic analysis of five tissues (heart, kidney, liver, lung, and spleen) from three breeds of minipig (ET-type, L-type, and Bama minipigs) and two breeds of pig (Duroc and Landrace). We identified 5,288 lncRNAs and found that their expression patterns distinguished breeds more prominently than protein-coding genes, suggesting the existence of different evolutionary constraints between them. Based on differential expression analyses, we identified tissue-common lncRNAs (tcDELs) that exhibited consistent expression differences between minipigs and pigs, as well as tissue-specific lncRNAs (tsDELs) with unique expression patterns in individual minipig tissues. Expression correlation analysis and functional enrichment of associated protein-coding genes revealed that these lncRNAs are involved in a wide range of biological processes. Notably, tcDELs were linked to pathways related to organ size and gene regulation across tissues, while tsDELs were associated with physiological functions specific to each tissue. These findings demonstrate that lncRNAs may contribute to both tissue-common and tissue-specific traits in minipigs, reinforcing their utility as animal models.